Reticulons 3 and 6 interact with viral movement proteins. (20th August 2022) - Tilsner, Jens; Kriechbaumer, Verena
Abstract: Plant reticulon (RTN) proteins are capable of constricting membranes and are vital for creating and maintaining tubules in the endoplasmic reticulum (ER), making them prime candidates for the formation of the desmotubule in plasmodesmata (PD). RTN3 and RTN6 have previously been detected in an Arabidopsis PD proteome and have been shown to be present in primary PD at cytokinesis. It has been suggested that RTN proteins form protein complexes with proteins in the PD plasma membrane and desmotubule to stabilize the desmotubule constriction and regulate PD aperture. Viral movement proteins (vMPs) enable the transport of viruses through PD and can be ER‐integral membrane proteins or interact with the ER. Some vMPs can themselves constrict ER membranes or localize to RTN‐containing tubules; RTN proteins and vMPs could be functionally linked or potentially interact. Here we show that different vMPs are capable of interacting with RTN3 and RTN6 in a membrane yeast two‐hybrid assay, coimmunoprecipitation, and Förster resonance energy transfer measured by donor excited‐state fluorescence lifetime imaging microscopy. Furthermore, coexpression of the vMP CMV‐3a and RTN3 results in either the vMP or the RTN changing subcellular localization and reduces the ability of CMV‐3a to open PD, further indicating interactions between the two proteins. Abstract : Different vMPs are capable of interacting with RTN3 and RTN6. Coexpression of the vMP CMV‐3a and RTN3 results in proteins changing subcellular localization and reduces the ability of CMV‐3a to open plasmodesmata.